Development of a methodological approach in order to solve the issue of forecasting complex indicators of renewable energy sources in the structure of the energy system of Ukraine with the use of the latest forecasting methods - Zaichenko, Z. V.; Trachuk, A. R. (Національний технічний університет "Харківський політехнічний інститут", 2024)
The authors evaluate the technological maturity of renewable energy technologies and their efficiency compared to traditional energy sources. Thanks to a broad analysis, the article makes an important contribution to the understanding of the prospects and factors for the successful implementation of renewable national energy in the conditions of modern energy challenges.
Keywords: systemic approach; energy balance; methods of analysis; development of wind energy; solar energy; bioenergy; дослідження; відновлювана енергетика; гідроенергетика; використання енергії